The burden of chronic diseases and patients' preference for healthcare services among adult patients suffering from chronic diseases in Bangladesh - Rashidul A. Mahumud; Marufa Sultana; Satyajit Kundu; Md. A. Rahman; Sabuj K. Mistry; Joseph K. Kamara; Mostafa Kamal; Mohammad A. Ali; Md. G. Hossain; Cristy Brooks; Asaduzzaman Khan; Khorshed Alam; et al. (Wiley, 2022)
Abstract Background Low‐ and middle‐income countries (LMICs) have a disproportionately high burden of chronic diseases, with inequalities in health care access and quality services. This study aimed to assess patients' preferences for healthcare services for chronic disease management among adult patients in Bangladesh. Methods The present analysis was conducted among 10,385 patients suffering from chronic diseases, drawn from the latest Household Income and Expenditure Survey 2016-2017. We used the multinomial logistic regression to investigate the association of chronic comorbid conditions and healthcare service‐related factors with patients' preferences for healthcare services. Results The top four dimensions of patient preference for healthcare services in order of magnitude were quality of treatment (30.3%), short distance to health facility (27.6%), affordability of health care (21.7%) and availability of doctors (11.0%). Patients with heart disease had a 29% significantly lower preference for healthcare affordability than the quality of healthcare services (relative risk ratio [RRR] = 0.71; 0.56-0.90). Patients who received healthcare services from pharmacies or dispensaries were more likely to prefer a short distance to a health facility (RRR = 6.99; 4.80-9.86) or affordability of healthcare services (RRR = 3.13; 2.25-4.36). Patients with comorbid conditions were more likely to prefer healthcare affordability (RRR = 1.39; 1.15-1.68). In addition, patients who received health care from a public facility had 2.93 times higher preference for the availability of medical doctors (RRR = 2.93; 1.70-5.04) than the quality of treatment in the health facility, when compared with private service providers. Conclusions Patient preferences for healthcare services in chronic disease management were significantly associated with the type of disease and its magnitude and characteristics of healthcare providers. Therefore, to enhance service provision and equitable distribution and uptake of health services, policymakers and public health practitioners should consider patient preferences in designing national strategic frameworks for chronic disease management. Patient or Public Contribution Our research team includes four researchers (co‐authors) with chronic diseases who have experience of living or working with people suffering from chronic conditions or diseases.